2005
DOI: 10.1002/j.2161-1882.2005.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Supporting the Increasing Severity of College Counseling Center Client Problems: Why Is It So Challenging?

Abstract: Since the late 1980s, college counselors have reported seeing increasing numbers of students who present with severe forms of emotional and psychological disturbance. However, little direct evidence has yet to demonstrate any trend in the level of severity of presenting problems. In this article, the authors explore methodological challenges for researchers who attempt to examine the question of increasing severity of client problems. Implications for college counseling centers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In the article mentioned above, Sharkin urges that Benton et al's findings be interpreted with caution, a theme he regularly echoes in other articles questioning the validity of the perception of increased psychopathology in college students. 9,10 Another challenge to Benton et al's work comes from a 2009 study conducted by Hoeppner et al, whose findings directly contradict Benton et al's. 11 Hoeppner et al examined the 12-year student-reported intake records of a university counseling center to test for trends in increased psychopathology.…”
Section: Prominent Studies That Probe the Perceptionmentioning
confidence: 73%
“…In the article mentioned above, Sharkin urges that Benton et al's findings be interpreted with caution, a theme he regularly echoes in other articles questioning the validity of the perception of increased psychopathology in college students. 9,10 Another challenge to Benton et al's work comes from a 2009 study conducted by Hoeppner et al, whose findings directly contradict Benton et al's. 11 Hoeppner et al examined the 12-year student-reported intake records of a university counseling center to test for trends in increased psychopathology.…”
Section: Prominent Studies That Probe the Perceptionmentioning
confidence: 73%
“…The nature of this finding is rather subjective and could be driven by the steadily climbing number of clients per year. As Sharkin and Coulter (2005) argued, college counselors could perceive severe client problems as more challenging under the pressure of a high workload.…”
Section: Introductionmentioning
confidence: 96%
“…This is not a viable method either because of the difference between client and therapists perspective. Changes in the client perceived distress may not necessarily reflect real changes (see Sharkin, 1997Sharkin, , 2005. They could be clouded by a higher reactivity to psychological symptoms due to media attention, high-profile cases or popular movies and therefore an increased willingness to rate higher on a given scale.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, there are also indications for stability in type and extent of psychological distress reported by clients of student counseling service [29] or even a decrease in self-reported mental health problems [5]. While it is possible that changes in the client-perceived distress may not necessarily reflect real changes, rather than the influence of media attention or high-profile cases on a higher reactivity to psychological symptoms [50], the necessity for more systematic research on the mental health of students is profound.…”
Section: Current Data On Mental Health Of Students Internationallymentioning
confidence: 99%